Pre-treatment With Ranibizumab Aggravates PDT Injury and Alleviates Inflammatory Response in Choroid-Retinal Endothelial Cells - Liu, Yang; Zhu, Min; Gong, Ruowen; Wang, Xin; Li, Lei; Xu, Gezhi (Frontiers in Cell and Developmental Biology, 2020)
Polypoidal choroidal vasculopathy (PCV) is the predominant subtype of exudative age-related macular degeneration in Asians. Although photodynamic therapy (PDT) is widely used for PCV treatment, its long-term beneficial effects are unsatisfactory. Accumulating clinical investigations suggest that combined therapy with anti-vascular endothelial growth factor (anti-VEGF) and PDT is superior to PDT monotherapy. However, the optimal time of anti-VEGF before or after PDT remains controversial, hence it needs to further explore the mechanism underlying combined therapy. PDT causes selective damage to endothelial cells, which determines its angio-occlusive efficiency, yet the impact of anti-VEGF on PDT-induced endothelial injury is unclear. Here, we found that pre-compared to post-treatment with anti-VEGF ranibizumab (rani) significantly aggravates PDT injury in the rhesus macaque choroid-retinal endothelial (RF/6A) cell line. PDT activates apoptosis, necroptosis and NLRP3 inflammasome in RF/6A cells. Pre-treatment with rani promotes PDT-caused apoptosis via triggering caspase 8-mediated extrinsic apoptosis, and caspase 8 might also play a pivotal role in the rani’s function of suppressing PDT-induced necroptosis and NLRP3 inflammasome activation. Our results implicate that pre-treatment with rani may enhance the angio-occlusive efficiency of PDT and alleviate endothelial inflammatory response, which gives it a great advantage over post-treatment.